Some Simpson's Riemann–Liouville Fractional Integral Inequalities with Applications to Special Functions. (23rd February 2022) - Nasir, Jamshed; Qaisar, Shahid; Butt, Saad Ihsan; Khan, Khuram Ali; Mabela, Rostin Matendo
Abstract : Based on the Riemann–Liouville fractional integral, a new form of generalized Simpson-type inequalities in terms of the first derivative is discussed. Here, some more inequalities for convexity as well as concavity are established. We expect that present outcomes are the generalization of already obtained results. Applications to beta, q -digamma, and Bessel functions are also provided.